THE ROLE OF SENSITIVITY LEVELS IN THE PATHOGENESIS OF ALLERGIC RHINITIS AND BRONCHIAL ASTHMA OF THE GROUP UNDER STUDY - Abdurasulovna, Ikramova Shakhnoza (Journal of Medical Genetics and Clinical Biology, 2024)
This article will provide feedback and feedback on the role of sensitivity levels in the pathogenesis of allergic rhinitis and bronchial asthma of the group under study. Allergic rhinitis and bronchial asthma are prevalent chronic inflammatory diseases that significantly impact the quality of life of millions of individuals worldwide. Both conditions are characterized by heightened immune responses to allergens, leading to inflammation of the respiratory tract. Recent research has shed light on the crucial role of Group 2 Innate Lymphoid Cells (ILC2s) in the pathogenesis of these diseases. Understanding the mechanisms by which ILC2s contribute to allergic rhinitis and bronchial asthma offers potential for novel therapeutic interventions